Situating Automatic Speech Recognition Development within Communities of Under-heard Language Speakers - Thomas Reitmaier (ACM CHI Conference on Human Factors in Computing Systems: CHI' 23, 2023)
In this paper we develop approaches to automatic speech recognition (ASR) development that suit the needs and functions of underheard language speakers. Our novel contribution to HCI is to show how community-engagement can surface key technical and social issues and opportunities for more efective speech-based systems. We introduce a bespoke toolkit of technologies and showcase how we utilised the toolkit to engage communities of under-heard language speakers; and, through that engagement process, situate key aspects of ASR development in community contexts. The toolkit consists of (1) an information appliance to facilitate spoken-data collection on topics of community interest, (2) a mobile app to create crowdsourced transcripts of collected data, and (3) demonstrator systems to showcase ASR capabilities and to feed back research results to community members. Drawing on the sensibilities we cultivated through this research, we present a series of challenges to the orthodoxy of state-of-the-art approaches to ASR development.